ANALISIS PERDAGANGAN INTERNASIONAL MELALUI MODEL POLITIK HECKSCHER-OHLIN TERHADAP KEPENTINGAN EKONOMI NASIONAL PESPEKTIF HUKUM EKONOMI ISLAM - Fadli Daud Abdullah; Chaerul Saleh; Fauzan Ali Rasyid; Doli Witro (UIN Mahmud Yunus Batusangkar, 2023)
This research analyzes international trade through the Heckscher-Ohlin political model towards national economic interests from an Islamic economic law perspective. This research uses qualitative methods with a text analysis approach. The data used is secondary, regarding the relationship between international trade, economic policy and national economic welfare. The research results show that the Heckscher-Ohlin (HO) theory is the main basis for studying the economics of international trade. This theory emphasizes differences in the scarcity of production factors between countries as the main factor influencing trade patterns. The main production factors in this theory are labor and capital. This difference in the scarcity of production factors encourages specialization in production, which helps increase the efficiency of resource allocation. Comparative advantage is basic in HO theory, where countries focus on producing goods they are able to produce at lower costs. This analysis also carries the HO Theory with Islamic economic law, which emphasizes the fairness of wealth distribution, business ethics, integrity, social welfare, balance and social justice, as well as individual moral responsibility in international trade. By combining these two approaches, international trade can provide sustainable economic and social benefits and is in accordance with Islamic ethical values.